COMBINED EFFECTS OF CARBIDE, CAVITATION AND THIN-SECTION SIZE ON THE CREEP-RUPTURE PROPERTIES OF A NICKEL-BASE SUPERALLOY - BALDAN, A (Carl Hanser Verlag, 1994)
The combined effects of thin-section size, carbide and cavitation dispersion on the creep rupture characteristics of the conventionally cast MAR-M002 superalloy have been studied at 1173 K/300 MPa. It was shown experimentally that the creep rupture life of the alloy is controlled by the (a(c)/a(o))ID ratio, where a(c) is the cavity size, a(o) the carbide particle size and D the diameter of the gauge section of specimen. Below a critical value (almost-equal-to 100 x 10(-6) mum-1) of this ratio the rupture life extends rapidly, whereas above the critical value of the ratio there is a slow increase in the rupture life. The effect of the (a(c)/a(o)/D ratio on the rupture life has been described using the existing theories which were developed for the prediction of stress concentrations at grain boundary particles.
Keywords: Gamma' Morphology; Resistance; Fracture; Particles; Growth